Screening Behavioural Disorders of Children Affected by Screentime with Real Computer Vision Technology - Firdaus, Zahrina alyani; Naufal, Adnan Faris; Andhini, Nur Intan Lia Putri; Rizky , Aisyah Shabrina; Rahmania, Ifitita Nayla; Asyifa. , Nabila Kultsum (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: In the development cycle of early childhood, several internal and external factors can influence changes such as disruption, delay or improvement. One of the external factors highlighted in this study is the application of screen time. Screen time in early childhood is highly recommended not to exceed 1 hour/day. This study aims to analyse the impact of screen time on behavioural disorders in the communication and personal social aspects of children aged 0-3 years at the Menur 6 Kartasura Children's Posyandu, using computer vision technology to monitor children's behaviour. Methods: The study used a quantitative study with a cross-sectional design. Statistical tests used the T-test. The number of samples is the total of the population aged 1-3 years as many as 24 respondents. The instruments used were interviews and observations with the ASQ-3 guidelines that had been developed in the form of computer real vision technology. Results: The results of the study showed that in the communication aspect there were 6 children in the category of needing stimulus and 18 children in the normal category, while in the personal social aspect there were 7 children in the category of needing stimulus and 17 others in the normal category. The analysis test of excessive screen time application is related to behavioural disorders, such as addiction, delayed language development, and social-emotional disorders. Conclusion: However, for behavioural aspects such as communication and personal social, there is no relationship between them. This finding emphasises the importance of parents' role in managing children's screen time to support optimal development.